2002
DOI: 10.1063/1.1519107
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative adsorption of NO upon Al(111): Orientation dependent charge transfer and chemisorption reaction dynamics

Abstract: The dissociative and abstractive chemisorption dynamics of NO on Al͑111͒ were studied. A higher sticking probability for the N end-on of NO onto Al͑111͒ was measured. In contrast, Auger electron experiments reveal stepped surfaces to be oxygen rich at low coverage after exposure to NO. Density functional theory calculations show ͑i͒ a few angstroms from the surface, an N end-on first collision geometry results in electronic structures consistent with charge transfer; ͑ii͒ there is stabilization on the surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…This can be understood as follows: only O 2 molecules close to parallel to the surface react at low E 0 while those perpendicular to the surface also contribute to the sticking at high E 0 , reducing S 0 ðHÞ=S 0 ðCÞ at higher E 0 . The reduction of S 0 ðHÞ=S 0 ðCÞ with decreasing E 0 at < 70 meV might be due to the steering effect [17,18], which redirects incoming molecules to favorable orientations and is known to be dominant at lower E 0 . The precursor-mediated process, which tends to dominate at low E 0 [6,19,20], can also cause this behavior.…”
mentioning
confidence: 99%
“…This can be understood as follows: only O 2 molecules close to parallel to the surface react at low E 0 while those perpendicular to the surface also contribute to the sticking at high E 0 , reducing S 0 ðHÞ=S 0 ðCÞ at higher E 0 . The reduction of S 0 ðHÞ=S 0 ðCÞ with decreasing E 0 at < 70 meV might be due to the steering effect [17,18], which redirects incoming molecules to favorable orientations and is known to be dominant at lower E 0 . The precursor-mediated process, which tends to dominate at low E 0 [6,19,20], can also cause this behavior.…”
mentioning
confidence: 99%
“…Oxygen is known to have a strong affinity with aluminum and understanding the details at the molecular level of the oxidation of aluminum has been, and remains, a challenge [34,35]. Experimental works [36,37] support the existence of dissociative adsorption of O 2 (yielding two O-atoms on the surface) and also abstractive adsorption yielding a single O-atom on the surface and an O-atom in the gas-phase. Libisch et al [34] identified abstractive adsorption as the dominant channel at low incident energies, i.e., at low temperatures.…”
Section: Oxygen (O 2 ) and Chlorine (Cl 2 )mentioning
confidence: 93%
“…The highly reactive nature of the N-end approach has also been demonstrated for NO/Al(111), and is understood well with DFT calculations. [82] Molecular orientation effects in reactive systems were also investigated extensively by Heinzmann's group, with measurements of the sticking probability and detection of gas-phase products on metal surfaces. [83] They found that the N-end approach is more reactive in the strongly bound NO/Ni(100) [83] and Pt(100) [84] systems, while in the reaction of oriented N2O with alkali-metal-adsorbed Pt(100) and Rh(100), [85] harpooning reactions occur preferentially with the O-end approach, resulting in the effective production of N2 molecules.…”
Section: Molecular Orientation Effectsmentioning
confidence: 99%